Medication Adherence and Associated Factors in Patients With Type 2 Diabetes: A Structural Equation Model - Huang, Jing; Ding, Shenglan; Xiong, Shuyuan; Liu, Zhiping (Frontiers in Public Health, 2021)
Background: The number of patients with type 2 diabetes (T2D) is increasing. Medication treatment is of great importance to stabilize blood glucose. Previous studies have reported that neuroticism, self-efficacy, and social support are factors associated with medication adherence, but few studies have fully investigated the mechanisms between these factors and medication adherence in patients with T2D. Purpose: To explore the prevalence of medication adherence and the factors associated with medication adherence in patients with T2D. Methods: A cross-sectional study consisting of 483 patients with T2D was conducted from July to December 2020. Questionnaires containing sociodemographic and clinical characteristics, the Morisky Medication Adherence Scale-8 (MMAS-8), the neuroticism subscale of the Eysenck Personality Questionnaire-Revised Short Scale (EPQ-RS), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Diabetes Management Self-efficacy Scale (DMSES) were used to collect data. The structural equation model (SEM) was used to test the hypotheses. Results: This study included 305 (63.1%) medication adherence and 178 (36.9%) medication nonadherence patients with T2D. Social support directly influenced medication adherence (β = 0.115, P = 0.029) and indirectly influenced medication adherence through self-efficacy (β = 0.044, P = 0.016). Self-efficacy directly influenced medication adherence (β = 0.139, P = 0.023). Neuroticism indirectly affected medication adherence through social support (β = -0.027, P = 0.023) and self-efficacy (β = -0.019, P = 0.014). Moreover, there was a sequential mediating effect of social support and self-efficacy on the relationship between neuroticism and medication adherence (β = -0.010, P = 0.012). After controlling for age and gender, similar results were obtained. The model fit indices showed a good fit. Conclusions: The medication adherence of patients with T2D needs to be improved. Neuroticism, social support, and self-efficacy had direct or indirect effects on medication adherence in patients with T2D. Healthcare providers should comprehensively develop intervention programs based on neuroticism, social support, and self-efficacy to improve medication adherence in patients with T2D.